2016
DOI: 10.17294/2330-0698.1409
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation and Stroke in Elderly Patients

Abstract: Follow this and additional works at: https://aurora.org/jpcrr Part of the Cardiology Commons, Cardiovascular Diseases Commons, and the Therapeutics Commons Journal of Patient-Centered Research and Reviews ( JPCRR) is a peerreviewed scientific journal whose mission is to communicate clinical and bench research findings, with the goal of improving the quality of human health, the care of the individual patient, and the care of populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…20 Specifically, while NVAF is associated with a 5-fold increase in the risk of ischemic stroke, this risk is 17-fold in patients with mitral stenosis. 6 In our review, the overall risk of AIS in patients with any type of VAF on DOAC was 3.5% (1511/42877), which is comparable to the risk in patients with NVAF on DOAC (3%) or on warfarin (3.7%) and in patients with VAF on warfarin (1.4-7%). 19 Although, in our review, AIS seemed to occur more often in patients with mitral valvular disease (5.3%), AIS did not occur at all (0%) in a cohort of VAF patients with severe valvular disease.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…20 Specifically, while NVAF is associated with a 5-fold increase in the risk of ischemic stroke, this risk is 17-fold in patients with mitral stenosis. 6 In our review, the overall risk of AIS in patients with any type of VAF on DOAC was 3.5% (1511/42877), which is comparable to the risk in patients with NVAF on DOAC (3%) or on warfarin (3.7%) and in patients with VAF on warfarin (1.4-7%). 19 Although, in our review, AIS seemed to occur more often in patients with mitral valvular disease (5.3%), AIS did not occur at all (0%) in a cohort of VAF patients with severe valvular disease.…”
Section: Discussionmentioning
confidence: 53%
“…atrial fibrillation in patients with prosthetic valves or aortic/mitral valve dysfunction), although the risk of AIS in these patients are up to 17-fold higher than the general population. 6 This scoping review aims (1) to examine and map the clinical cerebrovascular outcomes and (2) to identify knowledge gaps in patients with valvular AF treated with DOACs.…”
Section: Introductionmentioning
confidence: 99%
“…21 Overall, the report's large sample of patients hospitalized for acute mesenteric ischemia helps fill in existing knowledge gaps regarding atrial fibrillation, since the relatively low incidence of this complication has yielded limited published information. 22 In a timely review article, Dang et al 23 provide an update on stroke in atrial fibrillation, an important public health issue contributing to disability and death in elderly patients. 1 The authors review pathogenesis of thromboembolism in atrial fibrillation, define predisposing clinical characteristics and risk factors for stroke and summarize select issues in its management, including the use of novel anticoagulants and nonpharmacological approaches to reducing stroke risk in older-age patients with atrial fibrillation.…”
Section: This Issue Of the Journal Of Patient-centeredmentioning
confidence: 99%
“… 2 , 3 , 4 , 5 Moreover, its has been shown that individuals aged 80 years or older have >20% of atrial fibrillation–related strokes 5 and these are often more severe in terms of disability and mortality. 5 , 6 , 7 While oral anticoagulation therapy is the mainstay for thromboembolic cerebrovascular accidents prevention, 6 , 8 elderly patients are at increased risk of bleeding events 3 , 9 ; hence, these drugs are often underused, mainly because of advanced age or the perceived high‐risk of bleeding complications, falls, or even polypharmacy. 3 , 6 , 7 , 10 …”
mentioning
confidence: 99%